Madurez escolar en niños y niñas de preescolar de la Unidad Educativa Licto - Sigcho Miranda, Daniela Esthefania (2024)
This study on school maturity in preschool boys and girls from the Licto Educational Unit highlights the challenges posed by virtual education during the COVID-19 pandemic. Many parents needed more knowledge to support their children's development, adversely affecting school readiness. School maturity is a critical stage during the first five years of life, enabling the development of cognitive, affective, and motor skills essential for formal education. The objective was to identify predominant areas of school maturity, such as visual memory, visual-motor coordination, and auditory memory, and assess their prevalence in the children studied. A non-experimental design was used, observing real-world conditions without manipulating variables. The ABC School Maturity Test was administered to 24 children. Results revealed that 50% achieved high scores, demonstrating advanced cognitive development; 33% scored within the normal range but required reinforcement in specific areas, while 17% exhibited significant deficiencies. The findings showed a correlation between school maturity and academic performance, emphasizing the importance of cognitive, social, and emotional skills. Children with higher school maturity displayed better academic outcomes. The study recommends implementing early intervention programs to foster holistic development.